2016
DOI: 10.1590/2237-6089-2015-0088
|View full text |Cite
|
Sign up to set email alerts
|

Frontal lobe alterations in schizophrenia: a review

Abstract: When schizophrenia is studied as an essential topic in the field of neuropsychiatry, neuroscientists find that the frontal lobe is the most commonly involved area of the human brain. A clear picture of how this lobe is affected in schizophrenia is still lacking. We therefore recommend that further research be conducted to improve understanding of the pathophysiology of this psychiatric dilemma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 93 publications
3
35
0
Order By: Relevance
“…An interaction effect, accounting for age and sex, was not signi cant between group and FAA (f = 1.30, p = 0.253, η p 2 = 0.100). However, for between-subjects effects (schizophrenia vs. healthy control), we observed a signi cant difference in F4-F3 with the eyes-open condition (f [2,49] = 3.70, p = 0.032, η p 2 = 0.131). Alpha asymmetry in the schizophrenia group was lower than that in the healthy controls (-0.10 ± 0.04 vs. -0.05 ± 0.05, corrected p = 0.027, 95% CI = 0.01 to 0.10) ( Fig.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…An interaction effect, accounting for age and sex, was not signi cant between group and FAA (f = 1.30, p = 0.253, η p 2 = 0.100). However, for between-subjects effects (schizophrenia vs. healthy control), we observed a signi cant difference in F4-F3 with the eyes-open condition (f [2,49] = 3.70, p = 0.032, η p 2 = 0.131). Alpha asymmetry in the schizophrenia group was lower than that in the healthy controls (-0.10 ± 0.04 vs. -0.05 ± 0.05, corrected p = 0.027, 95% CI = 0.01 to 0.10) ( Fig.…”
Section: Resultsmentioning
confidence: 63%
“…There were no signi cant differences in F4-F3 with eyes open between patients with MDD and healthy controls (corrected p = 0.630, 95% CI = -0.02 to 0.07), or between MDD and schizophrenia patients (corrected p = 0.434, 95% CI = -0.02 to 0.08). There were no signi cant differences found in F4-F3 with eyes-closed (f [2,49] = 0.64, p = 0.532, η p 2 = 0.025), or in F8-F7 with eyes-open or -closed (f [2,49] = 0.96, p = 0.391, η p 2 = 0.038; f [2,49] = 0.11, p = 0.896, η p 2 = 0.004). In correlation analysis, there were no associations between alpha asymmetry and clinical symptoms (depression and F4-…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Recent studies have shown dysfunction of the precentral gyrus (PreCG) has long been thought to play a role in the impairments of voluntary movement associated with Schizophrenia and it has significantly reduced functional activity (FC) in patients with schizophrenia [3,4] . Also, schizophrenia is associated with volume deficits in PreCG [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies shows that Precentral gyrus (PreCG) has significant reduced of functional activity (FC) in Schizophrenia (SCH) patients [16,13]. Also, SCH is associated with volume deficits in Precentral gyrus [15].…”
Section: Introductionmentioning
confidence: 99%